UPAYA MEMBENTUK TRADISI KEDISIPLINAN SISWA DI SMP NEGERI 1 SAMBONG, KECAMATAN SAMBONG, KABUPATEN BLORA - Haji Kaswari; Adibah Jauhari; Abdul Rouf (FAI- Undar, 2020)
This study aims to find out how the efforts to form the tradition of student discipline. Formulation of the problem, first how the tradition of student discipline. second, how the school's efforts in shaping the tradition of student discipline. third is what inhibiting factors and supporting factors in the process of forming the tradition of student discipline.The results of the first study of the Disciplinary Tradition of students are very good. Second The school's efforts to form a tradition of student discipline are as follows: a) School bus procurement is carried out in collaboration with the community around the school independently. b) Prohibiting the carrying of motorized bicycles. c) Cooperation with the police d) Completion of facilities in schools, and othersInhibiting factors and supporting factors faced by the school in an effort to build students' disciplinary traditions are as follows: Supporting factors in the process of forming the tradition of student discipline. There is a school bus. Collaboration with the police. Supporting learning in the school environment, such as prayer rooms and sports fields. There is socialization for new students. There is a team that forms Teacher disciplineInhibiting factors in the process of forming students' disciplinary traditions. a) There are students with problems. b) There are still those who use motorized vehicles.